Study on interoperability problems among CAD/CAM systems in automotive industry - Daniyal, Hamdan (2004)
In automotive supply chain there are many different CAD/CAM systems that been used. Each system has its own proprietary data representation. As a result, product data are created and stored in multiple, frequently incompatible formats to other software's. Therefore, interoperability problems exist when files are being transferred between systems. Even with all the advances that have been made in the area of data transfer between CAD/CAM systems, this problem is still a major issue. This project studies the scenario on CAD/CAM data transfer problem particularly in automotive industry in Malaysia. Referring to others study at USA, Germany and Australia, a framework on how Malaysia's automotive industry can react proactively to the problems is proposed.